Bloy and Parry's : Principles of Criminal Law - Bloy, Duncan J., author 640830; Parry, Philip, author 640831; Molan, Michael T., author 640832; Lanser, Denis, author 640833 (London : Cavendish, 2000)
This text adheres to the basic principles of the earlier editions, focusing on the key principles of criminal law, major case law and new statutory provisions to provide a foundation for the comprehensive study of law. It aims to be thought-provoking and informative as well as constantly urging the reader to think further about the nature, extent and effectiveness of the criminal law.